2012
DOI: 10.3357/asem.2933.2012
|View full text |Cite
|
Sign up to set email alerts
|

Clothing Buoyancy and Underwater Horizontal Swim Distance After Exiting a Submersed Vehicle Simulator

Abstract: Flotation clothing (either Jackets or Overalls) is recommended for vehicle travel on ice because they do not impede underwater exit from a vehicle and allow significant horizontal underwater swim distance. An inflatable vest is not recommended because inappropriate premature inflation could increase exit impedance and decreased underwater swim distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This adjustable function can serve to reduce the obstruction to horizontal swimming upon development of the wearer's swimming skills. 4,14 Two market samples were selected for comparison with the knitted buoyant vest in this study (Figure 2). Market Sample A (Splash About, United Kingdom) is an item of swimwear with integrated buoyancy.…”
Section: Explorationmentioning
confidence: 99%
See 2 more Smart Citations
“…This adjustable function can serve to reduce the obstruction to horizontal swimming upon development of the wearer's swimming skills. 4,14 Two market samples were selected for comparison with the knitted buoyant vest in this study (Figure 2). Market Sample A (Splash About, United Kingdom) is an item of swimwear with integrated buoyancy.…”
Section: Explorationmentioning
confidence: 99%
“…The high buoyancy of integrated buoyant swimwear may inversely affect horizontal swim distance. 14 4 Adjustable buoyancy can be achieved by removing buoyant layers inside the vest. Donning and doffing 5 It is inconvenient to remove the entire suit in the event of restroom use or a diaper change.…”
Section: Prototype Development and Design Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the same authors found little difference in various forms of thermal protective flotation clothing regarding impedance of exit from a submerged simulator (McDonald & Giesbrecht, 2013b). Gagnon and colleagues (Gagnon, McDonald, Pretorius, & Giesbrecht, 2012;Gagnon, Pretorius, McDonald, Kenny, & Giesbrecht, 2013) found little difference in exit, escape, and horizontal underwater swim distance when using various thermal flotation clothing combinations while an inflatable vest did impede exit and underwater swim distance.…”
Section: Underwater Competenciesmentioning
confidence: 99%
“…Previous research and data on vehicle submersion accidents were reviewed (McDonald and Giesbrecht 2013b). A series of studies, involving more than 150 human-occupied vehicle, or simulator, submersions, was then conducted to answer several questions that had not been previously addressed (McDonald and Giesbrecht 2013a; Giesbrecht and McDonald 2010; Giesbrecht and McDonald 2011; Gagnon et al 2012; Giesbrecht et al 2017).…”
Section: Introductionmentioning
confidence: 99%